CHILD'S CONSENT AS A CONDITION IN IMPLEMENTING THE TRANSFER OF PARENTS' ASSETS TO CHILDREN (STUDY IN THE OFFICE OF NOTARY AND LAND DEED DEEDS MAKING OFFICIALS (PPAT) MALANG) - Sunardi, Sunardi; Muhibbin, Muhibbin; Adi, Surya (Universitas Islam Malang, 2022)
Article 1666 of the Civil Code defines a grant as an agreement whereby the grantor, at the time of his life, freely and irrevocably, surrenders something for the needs of the beneficiary who receives the handover. A land grant is a gift from one person to another without any substitute and is made voluntarily, without any contravention from the recipient of the gift, and the gift is made while the giver is still alive. However, a parent's gift to children in a family is not the least that can cause jealousy, even family division. This means that a grant that originally had a noble purpose as taqarrub and social care can turn into a family disaster and disaster. This is the duty of the PPAT and the Notary in providing legal counseling so that in making the grant deed later there will be no problem with lawsuits in court. Formulation of the problem 1) How is the process of transferring land grants to children according to statutory regulations. 2) How is the implementation of the transfer of parental assets to children at the Notary Office and Land Deed Making Officer (PPAT) Malang. 3) What are the considerations of the Land Deed Making Official (PPAT) for asking for the child's approval in making a grant deed. The method used is empirical research with a sociological juridical approach.The process of transferring land grants according to laws and regulations must be guided by Article 1682 of the Civil Code which states that no grant except as meant in Article 1687 can be made without a notarial deed, the minutes (original text) must be kept at the notary and if this is not done then the gift is invalid. In other words, every grant, both movable and immovable property (land) should use a notarial deed, specifically land rights, the process must or must use an authentic deed (PPAT deed).The implementation of the transfer of grants from parents to children at the Malang Notary Office and Land Deed Making Officer (PPAT) is based on interviews with the Malang notary and PPAT, that for the implementation of the transfer of land rights with the grant process, you must use a grant deed made by the Land Deed Making Officer. (PPAT), the grantor is subject to PPH tax and the grantor must pay the BPHTB tax (tax for acquiring land and building rights) and the PPAT is required to submit the grant deed to the Land Agency Office within 7 (seven) working days.Considerations of the Land Deed Making Officer (PPAT) for the approval of children in making a grant deed if the author of the analysis is from the theory of authority, then the making of a grant deed is the authority of the PPAT which is made by the parties and the PPAT is in accordance with Article 1868 of the Civil Code, but in making it must meet the requirements formal and material. Apart from that, as a basis for consideration or additional conditions in making a grant deed, PPAT Malang uses additional conditions with the consent of the child. With the aim that the child is considered to know and understand that the property has been donated to another relative, so as to minimize lawsuits or disputes in the future. Although basically a parent's gift to one of their children is actually permissible without having the permission or approval of the other child. Keywords: Grant, PPAT/Notary, Approval.